2016
DOI: 10.1002/2016ja022418
|View full text |Cite
|
Sign up to set email alerts
|

Dayside cosmic noise absorption at the equatorward boundary of auroral oval as observed from Maitri, Antarctica (L = 5; CGM 62.45°S, 55.45°E)

Abstract: On 02 April 2011, a couple of cosmic noise absorption (CNA) events were detected at Maitri, Antarctica (L = 5; CGM 63.14°S, 53.69°E) confining to nighttime and daytime. One of the two events that occurred during night hours was caused due to auroral substorm onset. The current study focuses on the later CNA event, which was recorded during daytime (10:00–13:00 magnetic local time (MLT), MLT = UT‐1, at Maitri, Antarctica). We refer to this CNA event as dayside CNA (DCNA) event. Absence of westward electrojet du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
(63 reference statements)
1
10
0
Order By: Relevance
“…CNA peaks occur at the auroral stations close to the time of those substorms, which is consistent with earlier observations [ Jelly and Brice , ; Kavanagh et al , ]. In fact, it is fairly well established that the occurrence of a substorm on the nightside is a necessary condition for the observation of dayside CNA [ Kavanagh et al , , ; Behera et al , ].…”
Section: Discussionsupporting
confidence: 87%
“…CNA peaks occur at the auroral stations close to the time of those substorms, which is consistent with earlier observations [ Jelly and Brice , ; Kavanagh et al , ]. In fact, it is fairly well established that the occurrence of a substorm on the nightside is a necessary condition for the observation of dayside CNA [ Kavanagh et al , , ; Behera et al , ].…”
Section: Discussionsupporting
confidence: 87%
“…Structureless patches confirm the occurrence of hiss, not chorus which is rare at L = 5 during afternoon hours. [ Behera et al , ] have shown that precipitation of particle at the day side can occur due to pitch angle scattering of subrelativistic electrons, especially in the prenoon sector. Nevertheless, the criteria that adopted in Behera et al [] have been followed in order to examine whether this is also a case of such day side CNA event or not.…”
Section: Discussionmentioning
confidence: 99%
“…[ Behera et al , ] have shown that precipitation of particle at the day side can occur due to pitch angle scattering of subrelativistic electrons, especially in the prenoon sector. Nevertheless, the criteria that adopted in Behera et al [] have been followed in order to examine whether this is also a case of such day side CNA event or not. There are two most important things viz., absence of westward electrojet over Maitri during substorm activity and a certain delay between the onset of substorm as observed in A L index and onset of CNA at Maitri qualify a CNA event to be called as a dayside CNA event at Maitri.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, such a decrease is not seen for electron fluxes in the energy range of 40–475 keV (Figures a and b). It is believed that the keV‐range electrons are generally precipitated by very low frequency (VLF) waves or chorus emissions (Behera et al, , ). A large decrease in the flux of these electrons between 8.5 and 10 UT was seen by both GOES‐13 and GOES‐15, and this decrease might be linked to VLF/chorus wave activity.…”
Section: Particle Loss During Emic Wave Activitymentioning
confidence: 99%